KEPEMIMPINAN TRANSFORMASIONAL PADA ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN KOMITMEN AFEKTIF - Heru Kurnianto Tjahjono; Fajar Prasetyo; Majang Palupi (Jurnal Manajemen dan Pemasaran Jasa, 2018)
The aims of this study are to explore a number of antecedents that affect the organizational citizenship behavior. The antecedent of organizational citizenship behavior is transformational leadership while affective commitment serves as a mediation variable. The respondents in this research are lecturers at private universities in Special Province of Yogyakarta Province. The number of samples used is 145 respondents by using purposive sampling. The analytical technique used in this study is Structural Equation Modeling (SEM). Based on the analysis, the influence of transformational leadership on the behavior of organizational citizenship is positively significant while transformational leadership to the affective commitment has significant positive effects, and the same also for affective commitment to behavior organizational citizenship which has a significant positive effect. The results of this study explain the phenomenon of organizational citizenship behavior among the lecturers which is increasingly demanding profession. The role of transformational leadership and affective commitment of lecturers are also becoming increasingly important.